Chiral primary amino alcohol organobase catalysts for the asymmetric Diels–Alder reactions of anthrones with maleimides. Issue 24 (31st December 2015) - Kumagai, Jun; Otsuki, Teppei; Subba Reddy, U.V.; Kohari, Yoshihito; Seki, Chigusa; Uwai, Koji; Okuyama, Yuko; Kwon, Eunsang; Tokiwa, Michio; Takeshita, Mitsuhiro; Nakano, Hiroto
Graphical abstract: Abstract: Simple chiral triethylsilyl-amino alcohol organocatalysts containing a bulky triethylsilyl group on the oxygen atom at the γ-position were designed and synthesized as new organocatalysts for enantioselective Diels–Alder reactions of anthrones with maleimides to produce chiral hydroanthracene Diels–Alder adducts in up to 99% yield and with up to 94% ee. Abstract : ( S )-2-Amino-1, 1-diphenyl-3-(diphenylmethylsilyloxy)propanol: C28 H29 NO2 Si [ α ]D 20 = −64.8 ( c 1.05, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S ) Abstract : ( S )-2-Amino-1, 1-diphenyl-3-(triphenylsilyloxy)propanol: C33 H31 NO2 Si [ α ]D 22 = −55.8 ( c 0.52, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S ) Abstract : ( S )-2-Amino-1, 1-diphenyl-3-(tripropylsilyloxy)propanol: C24 H37 NO2 Si [ α ]D 22 = −77.5 ( c 1.02, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S ) Abstract : ( S )-2-Amino-1, 1-diphenyl-3-(trihexylsilyloxy)propanol: C33 H55 NO2 Si [ α ]D 24 = −49.6 ( c 1.27, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S ) Abstract : ( S )-1, 1-Diphenyl-3-(triethylsilyloxy)-1-(trimethylsilyloxy)propane-2-amine: C24 H39 NO2 Si2 [ α ]D 19 = −43.8 ( c 1.05, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S ) Abstract : N -Dimethyl-( S )-2-amino-1, 1-diphenyl-3-(triethylsilyloxy)propanol: C23 H35 NO2 Si [ α ]D 23 = −29.7 ( c 0.74, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S ) Abstract : N -Benzyl-( S )-2-amino-1, 1-diphenyl-3-(triethylsilyloxy)propanol: C28 H37 NO2 Si [ α ]D 24 = −24.8 ( c 1.05, CHCl3 ) Source of chirality: Serine Absolute configuration: (2 S )